Peningkatan Kekuatan Struktur Eksisting dengan Penguatan Struktur Menggunakan CFRP & Concrete Jacketing - Anis Rosyidah; Finantika Sekar Asmara; Muhamad Ziddan (TEKNIKA, 2019)
Some building is not designed with structural design rules. Contractors often use their experience to determine the dimensions of building structures. Buildings that are designed not by the rules of structural design will have a fatal impact. This study aims to calculate the capacity of the existing structural components of the building capacity after addition of earthquake loads and determine the correct method of strengthening the structure. The study was conducted by analyzing existing buildings with the addition of earthquake loads. Strengthening the structure is needed by comparing the existing strength with the strength of the plan, the structural reinforcement method used is carbon fiber reinforced polymer (CFRP) and concrete jacketing because those methods have merit to the effectiveness and conditions of the existing building. The results showed that the column structure was strong in accepting workloads. The beam structure requires strengthening the structure because the nominal strength of the existing beam is less than the strength of the plan. Existing beams require additional shear and flexural strength, averaging 76,90% and 90,92%. The results also showed the beam moment strength after being given an increase of 202,82% and 265,65% for each method. The beam shear strength after being given an increase in strength of 352,78% and 411,66% for each method.